Unpopular culture - Lüthe, Martin; Pöhlmann, Sascha (Televisual culture., 2016)
This volume introduces a new concept that boldly breaks through the traditional dichotomy of high and low culture while offering a fresh approach to both: unpopular culture. From the works of David Foster Wallace and Ernest Hemingway to fanfiction and The Simpsons, from natural disasters to 9/11 and beyond, the essays find the unpopular across media and genres, analysing the politics and aesthetics of a side to culture that has been overlooked by previous theories and methods in cultural studies.